Avoiding Despicable Morals, namely Miserliness and Hypocrisy Through the Story of Tsa'labah Ibn Hatib Al-Ansari - Maimunah Munthe; Siti Ardianti; Siti Zahra (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
A popular story spread in Islamic society about Tsa'labah ibn Hatib, a companion of the prophet who became miserly and hypocritical when His prayer was granted by Allah Almighty. Tsa'labah was one of the companions of the prophet who was initially very devoted to the Commandments of Allah Almighty and diligent in worshiping to the mosque when he was still poor, while the purpose of this study was to find out what despicable traits or morals existed in Tsa'labah so that he was said to be a person who Damnated by Allah Almighty, This research is a literature study research, namely research by reviewing and examining sources that are relevant to the research being carried out which is taken from several books and journals that are relevant to the title that the researcher wrote and raised to be researched, The results of this study are a form of presentation of researchers about avoiding despicable morals, namely miserliness and hypocrisy through the example of the story of Tsa'labah where in this story Tsa'labah shows that he was one of the companions of the Prophet who was originally devoted to Allah Almighty but because he was kufr not grateful for the blessings given by Allah made him forget to carry out the command of Allah Almighty, namely zakat, as for the despicable nature or morals in Tsa'labah that we should avoid is miserly, kufr delicious, arrogant, greedy, and break promises.